ATAC-seq on Sorted Adult Mouse Neurons - Erin Clark; Yasuyuki Shima; Sacha Nelson (Bio-Protocol, 2019)
Transcription regulation is a key aspect of cellular identity established during development and maintained into adulthood. Molecular and biochemical assays that probe the genome are critical tools in exploring mechanisms of transcription regulation and cell type identity. The mammalian brain is composed of a huge diversity of cell types with distinct properties and functions. To understand these specific roles, it is necessary to selectively target cell populations for study. However, the need to selectively study restricted cell populations poses a challenge in neurobiology. It is often difficult to collect sufficient cellular input for many standard biochemical and molecular assays. Recently, important advances have been made to scale assays down, opening up new frontiers to explore molecular mechanisms in neurons. Concurrently, methodologies for preparing neurons for such assays has advanced taking into consideration specific methods to preserve the cell biology meant to be assayed. Here we describe a method for preparing live neurons from adult brain tissue for the Assay for Transposase Accessible Chromatin (ATAC).